DINAMIKA PENYUSUNAN RENCANA PEMBANGUNAN JANGKA MENENGAH KEPENGHULUAN PASIR PUTIH KECAMATAN BALAI JAYA KABUPATEN ROKAN HILIR TAHUN 2018-2023 - Triono, Agus; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research is motivated by a problem in the preparation of the PasirPutih Village Medium Term Development Plan. This study aims to describe the dynamics that occur in the process of preparing the White Sand Village RPJM. This study uses development planning theory, village development planning, and village government. Data sources used were research informants and documents. Data collection techniques used interviews and documentation. To describe problems in this study qualitative data analysis was used.The results of this study indicate that in the seven stages of the village RPJM preparation process, five stages occur dynamics, namely: the stages of forming the village RPJM drafting team, the stage of assessing the situation of the Village, the stages of compilation of village development plans through village deliberations, the stages of compilation of village development plans through village musrembang, and the stages of determining and changing the village medium term development plan. Two stages that did not occur were dynamics, namely the alignment of the direction of the district development planning policy, and the stage of drafting the village medium term development plan. Keywords: Compilation, Village RPJM, Dynamics